Application of sequential extraction analysis to electrokinetic remediation of cadmium, nickel and zinc from contaminated soils - Giannisa, Apostolos (2016)
An enhanced electrokinetic process for the removal of cadmium (Cd), nickel (Ni) and zinc (Zn) from contaminated soils was performed. The efficiency of the chelate agents nitrilotriacetic acid (NTA), diethylenetriaminepentaacetic acid (DTPA) and diaminocycloexanetetraacetic acid (DCyTA) was examined under constant potential gradient (1.23 V/cm). The results showed that chelates were effective in desorbing metals at a high pH, with metal–chelate anion complexes migrating towards the anode. At low pH, metals existing as dissolved cations migrated towards the cathode. In such conflicting directions, the metals accumulated in the middle of the cell. Speciation of the metals during the electrokinetic experiments was performed to provide an understanding of the distribution of the Cd, Ni and Zn. The results of sequential extraction analysis revealed that the forms of the metals could be altered from one fraction to another due to the variation of physico-chemical conditions throughout the cell, such as pH, redox potential and the chemistry of the electrolyte solution during the electrokinetic treatment. It was found that binding forms of metals were changed from the difficult type to easier extraction type.